Effect of silice to the attack of lizards and birds in soybean cultivars in closed / pantanal ecotton (Research, Society and Development, 2020)
The use of silicon is one of the prevention and control measures that are taken to reduce pest infestation and attack, it acts on the cell wall, generating a protective layer to the penetration of phytopathogens and insects, as well as improving the architecture of the plant. The objective of this study was to evaluate the effect of silicon on the attack of caterpillars and bedbugs on soybean in the Cerrado / Pantanal ecotone region. The experimental design was a randomized complete block design with four replications, totaling 540 m². The plots were represented by the following soybean cultivars: SYN13671 IPRO, P97Y07, P97R21, BG4272, S1163RR and S9070RR, the subplots being formed in the application or not of foliar silicon, whose source was KSi (11% K2O and 25% of Yes). The evaluations were carried out weekly, occurring from 56 to 133 days after sowing of the cultivars, where, with the aid of the beat cloth, monitoring was performed to identify the insect pests, and later annotated in a spreadsheet to perform the data counting. All data analyzes were performed with the Rbio software, the means of analysis of variance were compared by the Tukey test at 5% probability. The application of the formulation used in the dosage of 500 mL ha-1 did not influence the decrease in the population incidence of insect pests studied in this study.